FORENSIC ASPECTS OF INTERROGATING CORRUPTION SUSPECTS MODERN TACTICS AND PROFILING (World Bulletin of Management and Law, 2026)
This study examines the forensic, psychological, and procedural aspects of interrogating individuals suspected of corruption-related crimes in Uzbekistan, drawing on modern investigative interviewing models and international best practices. The research aims to determine which interrogation tactics are legally acceptable, practically applicable, and effective in corruption investigations within the national context. A mixed-methods approach was applied, combining comparative legal analysis with an empirical assessment conducted through a focus group of 15 experienced investigators